ChemInform Abstract: 3‐Azidothieno[2, 3‐b]pyridine Thermolysis as a Route to Novel peri‐Anellated Heterocyclic Derivatives — Benzo(furo)thieno[2, 3, 4‐ij]‐2, 7‐naphthyridines. Issue 33 (August 2015) - Vasilin, Vladimir K.; Kanishcheva, Eugeniya A.; Stroganova, Tatyana A.; Krapivin, Gennady D.
Abstract Various title compounds (V) and (IX) are obtained by thermolysis of alkyl(aryl) 3‐azidothieno[2, 3‐b]pyridine‐2‐carboxylates containing an aryl or heteroaryl substituent at position C‐4 of the thienopyridine core (IV) and (VIII).